Muon-decay parameters from COHERENT - Bresó Pla, Víctor; Cruz-Alzaga, Sergio; González-Alonso, Martín; Prakash, Suraj (Physical review letters, 2025)
We demonstrate that measurements of coherent elastic neutrino-nucleus scattering at spallation sources are valuable probes of muon-decay physics. Using COHERENT data we derive the first direct constraint on the Michel parameters governing the ¯𝜈𝜇 energy distribution. We also discuss future sensitivities, the implications for the Lorentz structure of the interactions mediating muon decay, and the application to other neutrino-production mechanisms like pion decay.
Gesehen am 10.02.2026